KUALITAS PELAYANAN, KEPUASAN DAN LOYALITAS MAHASISWA - Firmansyah, Ade (Jurnal Ilmu Administrasi Negara, 2016)
Quality of Service, Student Satisfaction and Loyalty. The study aims to determine the effect of service quality and student satisfaction to loyalty student at the University library Riau. The population is all students at the University of Riau. Samples taken as many as 98 students to make use of the formula slovin. The technique of collecting data using questionnaires, interviews and observation. Analysis of data using path analysis (path analysis). The results showed that the quality of service, satisfaction student and loyalty to Riau University library has been good. The quality of service can be a direct affect on student loyalty with r 0.435 and indirectly also affect the service quality of student satisfaction affects loyalty with r 0,535 students.